PENGARUH RELATED PARTY TRANSACTION DAN MULTINATIONALITY TERHADAP PENGHINDARAN PAJAK - Zulha Nandita (2021)
This study aims to determine the effect of related party transactions and multinationality on tax avoidance. This research is quantitative research using secondary data in the form of the company's annual report. The research sample comes from manufacturing companies listed on the Indonesia Stock Exchange for the period 201-2020. Based on the sampling techniquw obtained sample as many as 48 samples in this study. The test of this research uses panel data regression analysis through STATA tool with a significance level of 5%. The results of the research hypothesis test obtained are related party transaction-sales and related party transaction-loans have a significantly positive effect on tax avoidance, while related party transactions-purchase have a significantly negative effect and multinationality does not have a significant effect on tax avoidance.